Child Health Screening Application with Body Mass Index Standard Assessment of Child Nutritional Status using Agile Development - Ahmad Nursodiq; Nurfiqih Nurfiqih; Zainudin Zainudin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Nutrition is a substance that influences the development of the human body so that the body's functions run as they should. Nutritional status is a condition where nutritional intake is balanced with the body's needs. If a child has excess nutritional intake, it is not good for the body. Posyandu officers record children's weighing data, detect the child's nutritional status and then provide a report on the child's nutritional data to the community health center. Data collection on children's nutritional status at the Posyandu is still manual in the form of data being recorded on paper, which can cause data to be lost, damaged, torn, and nutritional data. children are scattered, or piled up with other information. Therefore, we need a web-based application for checking children's nutritional status with the Body Mass Index (BMI) standard for assessing children's nutritional status, so that children know the ideal weight and height to prevent obesity or malnutrition so that children can adopt a healthy lifestyle. The research method used in this research is Agile Development Software which consists of requirements gathering, design, development, testing, implementation and evaluation. Then, in making this application, we also used the CodeIgniter 3 Framework. This application is expected to help Posyandu officers and parents in collecting data and detecting children's nutritional status based on Body Mass Index standards.